Spatial-temporal variability of the chlorophyll «a» concentration in the Krasnodar reservoir according to the satellite images’ data - Andrey A. Laguta; Anatoly V. Pogorelov (Водное хозяйство России: проблемы, технологии, управление)
The Krasnodar Reservoir has undergone significant transformations during its operation since 1973. As a result, of active delta formation of the Kuban and Belaya rivers, the reservoir was divided into two autonomous reservoirs, its area decreased by 35 %. The study is aimed at determining the significance of the eutrophication factor in the transformation of the Krasnodar Reservoir.